TINJAUAN KEBUTUHAN SDM BERDASARKAN METODE WISN DI UNIT REKAM MEDIS DEPARTEMEN KIARA RSCM - Abdul Chamid; Yuyun Yunengsih (Bajang Institute, 2021)
Method of calculating human resource needs based on workload (WISN) is a method of calculating health human resource needs based on the real workload carried out by each category of health human resources in each work unit in health care facilities. The purpose of this study was to determine the need for human resources based on workload standards in the medical record work unit. The research method used is descriptive research with data collection techniques, classification, data processing/analysis, making conclusions and reports. Based on the results of the study, it was found that the total number of personnel needed by the patient registration section of the Kiara Department of Dr. Cipto Mngunkusumo Hospital was 6 people, currently in the field there are 4 registration officers. The personnel needed by the medical record unit of the Kiara Department of Dr. Cipto Mangunkusumo Hospital are 11 people, while the reality in the field is that there are 7 medical record officers. There should be an increase in the number of medical record personnel by 4 people according to the calculation using the WISN method.